PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN HIMPUNAN KELAS VII MTs BERBASIS UNITY OF SCIENCES - Dyan Falasifa Tsani (Integral : Pendidikan Matematika, 2018)
The study of development was based on a dichotomy of science based on the perception of the students of science (including mathematics) and the science of religion. The purpose of this study was to develop a mathematics learning modulebased on Unity of sciences. The research subjects were students of class VII-A MTsHasyim Asy'ari Bangsri, amounting to 37 students. The results of this study are thecompilation of modules based on Unity of sciences that were developed followingthe ADDIE model which consists of 5 main stages, namely (A) analysis, (D) essay,(D) e-development, (I) implementation, and (E) evaluation. This module was testedfor validity by three mathematics education lecturers at UIN Walisongo Semarangand one MTs teacher Hasyim Asy'ari Bangsri, and obtained an average percentage of85% in the quite valid category and needed a little revision. The practicality resultsof the module are obtained from the assessment of the responses of students andteachers who get an average value of 3.3 and 3.2 of the maximum score of 4 withgood categories, so that the module is practical to use. Assessment of cognitiveaspects of students to express the effectiveness of the module, obtained from the pretest and posttest values analyzed by n-gain, and the n-gain value of 0.63 from themaximum score of 1 in the medium category. Based on the results of this research, itcan be stated that the mathematics learning module on the subject of class VII MTsbased on Unity of sciences has good quality.Keywords: modules, module development, sets, unity of sciences